Sistem Pendukung Keputusan Pemilihan Duta Prestasi Menggunakan Metode SMART (Studi Kasus Smk Negeri Sumsel) - Fadhlullah, Muhammad Iqbal; Pito Pratama, Ajis; Saputra, Andri; Effendi, Benedictus (MDP Student Conference, 2024)
Achievement ambassadors are school icons who are able to be role models and be a good instance to others and share information about the school’s potential with the wider community so that they are interested in the school. The selection of achievement ambassadors at SMK Negeri Sumsel is still subjective (individual) based on the jury’s assaessment. With this subjective assessment process, the author encountered a problem, by the frequent occurrence od miscalculations in determining achievement ambassadors. Based on the problem, the author designed and implemented a decision support system for selecting achievement ambassadors using a simple multi attribute rating method as a calculation method and a prototype as a system development method. By creating this application, the author hopes to be able to overcome that accur during the process of selecting achievement ambassadors.